Discourse Analysis: Contextualism and Reductionism - Majidi, Setareh (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
For the past twenty to thirty years, a good part of the domain of linguistics has been occupied by what has been called discourse analysis. Whereas syntax and semantics are concerned by the sentence and the units from which the sentence is built, discourse analysis claims that interpretation cannot accounted for at the level of the sentence and that a bigger unit, such as discourse should be used to account for language interpretation. We want to show here that discourse is not, in any sense, a well defined object and that, though it is certainly necessary to analyze how a given sequence of sentences is processed and understood, the notion of discourse, A and related notions such as coherence does not have much to say about it. We rely on epistemological considerations about the necessity of a moderate reductionism and sketch on account of linguistic interpretation which accounts for contextual factors in linguistic interpretation through the notion of utterance (vs. sentence) and a development of Sperber & Wilsons Relevance Theory.